Tepung Umbi Bawang Dayak (Eleutherine palmifolia (L) Merr) Sebagai Feed Additive Burung Puyuh (Coturnix-coturnix japonica) - Dela Heraini Heraini (Jurnal Ilmu dan Industri Peternakan, 2023)
Quail is a bird that has a medium body size and is relatively unable to fly like other birds. Increasing the quail population must be balanced with good maintenance management, especially during the growth phase. An alternative to improve growth performance is to provide feed additives in the ration, one of which is dayak onion bulbs. The purpose of this study was to determine the effect of giving dayak onion flour (Eleutherine palmifolia, (L) Merr) as a feed additive on the growth performance of quail (Coturnix-coturnix japonica). This study used a completely randomized design (CRD) consisting of 5 treatments and 5 replications, each treatment consisting of 7 quails so that the total number of quails was 175. The treatments used in this study were commercial feed (PK) and dayak onion flour (TUBD) consisting of P0 (100% PK), P1 (100% PK + 1% TUBD), P2 (100% PK + 2% TUBD ), P3 (100% PK + 3% TUBD), and P4 (100% PK + 4% TUBD). Parameters observed were feed consumption, body weight gain, feed conversion, weight of first laying eggs. The results of the analysis of variance (Anova) showed that the administration of dayak onion bulb flour had no significant effect (P>0.05) on the growth performance of quail including feed consumption, body weight gain, feed conversion, weight of first laying brood. The results showed that the highest feed consumption occurred at P0 (100% PK) = 115.90 gram/head/week; highest body weight gain occurred at P2 (100% PK + 2% TUBD) = 22.70 gram/head/week, the lowest feed conversion occurred at P4 (100% PK + 4% TUBD) = 5.28, and body weight 123 .4 grams/head. Giving dayak onion Flour (TUBD) to improve quail growth performance on feed consumption, body weight gain, feed conversion, and first egg laying weight did not have a significant effect.